Telomere is shortened in patients with irritable bowel syndrome in the Chinese population. Issue 9 (25th June 2022) - Zhang, Yuan; Fu, Fengyihuan; Zhang, Liangjie; Zhang, Weihong; Chen, Lin; Zhang, Yong; Chen, Wenji; Du, Yanlei; Chen, Shuzhen; Zhan, Qi; Feng, Zhiqiang; Xu, Haoming; et al.
Abstract: Background and Aim: Telomere shortening is an accepted indicator of aging. Many studies have investigated an association between leukocyte telomere length (LTL) and psychiatric disorders. Mental or psychological factors could be an important cause of irritable bowel syndrome (IBS). However, there are currently few research evaluating correlations between LTL and IBS. Methods: We examined associations between LTL and IBS using quantitative polymerase chain reaction in independent cohorts, including 205 patients with IBS and 189 healthy controls. Furthermore, we examined whether mental or psychological factors, types of IBS, duration of IBS and antidepressants had an association with LTL in patients with IBS. Results: Among total samples, patients with IBS presented shorter LTL when compared to healthy controls ( P < 0.0001). Moreover, in subgroup analyses of patients with IBS, not only the LTL in patients with IBS caused by mental or psychological factors was shorter ( P < 0.0001), but also in patients with IBS that were caused by other factors ( P = 0.0082). Furthermore, LTL in patients with IBS who had taken antidepressants for more than 1 month was longer than that in patients with IBS who did not take antidepressants or took for less than 1 month ( P < 0.0001). Conclusions: This is the first study to describe the relationship between LTL and IBS. This study showed significantly shorter telomeres in patients with IBS. Our findings suggest that LTL may hold the potential to serve as a predictor of IBS diagnosis.